EDUCATIONAL SIGNIFICANCE OF TERMIZI'S PSYCHOLOGICAL THOUGHTS - A. B. Kadirova (Journals Park Publishing, 2024)
Al-Hakim al-Termizi is a thinker who tried to shed light on the positive aspects of events and phenomena that affect the human psyche, as well as the didactic aspects of the written sources of Islam, more precisely the rules. The wisdom of Hakim Termezi is that he determined that the 12 years of the muchal would be under the influence of the 12 celestial constellations, and that earthly life would be governed by this constellation.
Keywords: Enlightenment, mysticism, theology 'Hakimiya', hadith studies, the power of the human mind, discussion and debate, the rules of etiquette, will control, soul nurture.